Development of SETS-Based Teaching Materials in Acid-Base Accompanied by Critical Thinking Exercises and Moral Forming - Rahmat Rasmawan (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2020)
This study aims to produce SETS-based teaching materials in acid-base concept that can foster students' critical thinking skills and establish their morale. This study is Research and Development (R & D) refers to the Borg and Gall model, which has been modified into five stages; preliminary study, preparation of product draft, validation and revision of product draft, legibility test, and product draft revision. As the instrument, this study was using a questionnaire about resistances and obstacles, observation sheets in learning, interview guidelines, validation sheets of teaching materials draft, and legibility response questionnaires. Data obtained from questionnaires, learning observation sheets, and interview guidelines were analyzed descriptively qualitatively to get the representation of the learning process that has been conducted so far. The validation sheet and legibility response questionnaire were analyzed quantitatively to determine the validity and legibility levels of teaching materials. The results of expert validation show that the developed teaching materials have a direct link between science, the environment, technology and society in solving problems related to daily life and the students as users give positive responses to the developed teaching materials in terms of content, appearance, novelty, problems, direction and work instructions. Thus, teaching materials developed are valid and proper to be used in the learning process